2016
DOI: 10.1177/1049909116658022
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Spanish-Language Hospice Video

Abstract: The nation faces a persistent issue of delayed access to hospice care. Even though hospice enrollment is considered to be one of the most difficult medical decisions, physician clinics and hospitals lack tools for helping patients/families faced with making decisions about enrollment. Health-care literature lacks discussion of development of decision-making aids in the context of hospice decisions for minority ethnic groups, even though those groups have decisional needs that may differ from those of non-Hispa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…Introduction to death, palliative care, and hospice. Eighteen studies (13 studies for health professionals, two for family caregivers, two for volunteers, and one for indigenous community carers) covered the following aspects: definitions of palliative care, hospice, and death in medical and legal terms [25,26,27,28,29,30,31,32,33,34,35,36]; core hospice concepts such as supporting not only the patient but also caregivers and interdisciplinary practices [37]; the theory of 'circle of care', philosophies, and principles of palliative care [38,39,40]; death as a developmental story [41]; and trajectories of various end-stage diseases [42]. While the content of this theme largely followed the medical and legal terms of death, the PCE for Northern Plains American Indians (NPAIs) delivered the program by consulting with the targeted indigenous community and employed indigenous language to introduce the concept of death.…”
Section: Themes Common To Target Audiencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Introduction to death, palliative care, and hospice. Eighteen studies (13 studies for health professionals, two for family caregivers, two for volunteers, and one for indigenous community carers) covered the following aspects: definitions of palliative care, hospice, and death in medical and legal terms [25,26,27,28,29,30,31,32,33,34,35,36]; core hospice concepts such as supporting not only the patient but also caregivers and interdisciplinary practices [37]; the theory of 'circle of care', philosophies, and principles of palliative care [38,39,40]; death as a developmental story [41]; and trajectories of various end-stage diseases [42]. While the content of this theme largely followed the medical and legal terms of death, the PCE for Northern Plains American Indians (NPAIs) delivered the program by consulting with the targeted indigenous community and employed indigenous language to introduce the concept of death.…”
Section: Themes Common To Target Audiencesmentioning
confidence: 99%
“…Care for the family. The areas discussed in 12 studies (11 for healthcare professionals and one for volunteers) included: giving the bad news to the family [25]; engaging and interacting with the family and caregivers [25,33,46,61]; family involvement in decision making [43]; family-centred care [44]; interacting with Latino caregivers [37]; care for the family, family caregivers, and volunteers [38,48,54]; family assessment [61]; and family perspectives on giving and receiving care [59].…”
Section: Themes Common To Target Audiencesmentioning
confidence: 99%
“…In our study, hospice providers reported that visual learners will benefit the most from videos, and they may provoke conversations with family caregivers. Studies have reported that when participants can identify with the video, learning through modeling can take place, 30,31 and participants value the visual as opposed to words or text. 22 It is difficult to construct preferences where we have few prior experiences or only limited understanding of potential futures states.…”
Section: Discussionmentioning
confidence: 99%
“…18 These barriers are addressed by our seminar if it is used to educate HCPs and if the telenovela is used as a resource to educate Latino caregivers. A study by Chung et al 19 demonstrated the development and effectiveness of a video as a form of decision support for Latinos, in particular those with low education and limited English proficiency who are least likely to have ever heard of hospice. Similarly, our telenovela is culturally sensitive, increases awareness in core concepts, and also, HCPs report that they may use it for education and to improve patientprovider communication.…”
Section: Discussionmentioning
confidence: 99%